(untitled) (Journal of Biomedical Investigation, 2025)
Background: Pain is a complex, multifaceted experience that extends beyond mere nociception. The neuromatrix theory, introduced by Melzack, reframes our understanding of pain by conceptualizing it as an output of a widely distributed neural network influenced by sensory input, cognitive evaluation, and emotional state. Aim: This scoping review examined the application of the neuromatrix model within physiotherapy, evaluating its relevance as a comprehensive, non-pharmacological framework for managing diverse pain conditions. Methods: A systematic search was conducted between January 15 to january 30 2025, across PubMed, Science Direct, and Google Scholar using predefined keywords. After screening 1,273 articles and assessing 127 full-text papers, 36 studies met the inclusion criteria, including randomized controlled trials, observational studies, qualitative research, and mixed-methods designs. The review mapped how physiotherapists apply neuromatrix-informed strategies-such as movement therapy, pain neuroscience education, manual techniques, and psychosocial interventions-to address the multidimensional nature of pain. Results: Findings underscore a shift from biomedical to biopsychosocial approaches, highlighting the importance of therapeutic alliance, patient beliefs, and neuroplasticity in modulating pain perception and promoting recovery. Interventions targeting chronic pain conditions such as low back pain, fibromyalgia, and phantom limb pain showed evidence of altered brain activity and pain modulation consistent with neuromatrix principles. Conclusion: However, study heterogeneity and limited high-quality trials suggest that further research is needed to confirm these outcomes and support broad implementation.